Financial Help Seeking and Career Adaptability Model Using Artificial Neural Network for MSMEs to Support Economic - Endang Retnoningsih; Samin Samin (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2025)
Help seeking and career adaptability are important factors that influence the success of achieving goals. The study aims to develop a model of the relationship pattern between financial help seeking and career adaptability specifically for MSMEs. Help seeking as an input variable and career adaptability factors as output variables, each variable is used as a model in an Artificial Neural Network. The study considers the relationship between financial help seeking and career adaptability, namely financial help seeking helps MSMEs obtain information and support from other parties to overcome problems faced and career adaptability as a result of MSMEs overcoming problems to survive running their businesses. The development of the financial help seeking and career adaptability model in the study used the Artificial Neural Network (ANN) algorithm classification method. The model built can be useful for predicting how MSMEs seek help solutions when experiencing financial difficulties related to developing their businesses and the sustainability of continuing their businesses.